Performance of Hybrid ARQ for NDMA Access Schemes with Uniform Average Power Control - Ganhão, Francisco (2018)
Traditionally, a packet with errors, either due to channel noise or collisions, is discarded and needs to be retransmitted, leading to performance losses. Network Diversity Multiple Access (NDMA) handles collisions by combining a multipacket detection scheme with time diversity. In NDMA, the Base Station (BS) forces mobile terminals (MTs) to transmit P copies of each packet when P MTs collide. Diversity combining is limited to P copies of the packets, not allowing it to adapt to severe errors due to channel noise. This paper considers a multipacket detection scheme recently proposed, which reduces the Packet Error Rate (PER) when more than P packet copies are available. In this paper, a Hybrid-ARQ NDMA (H-NDMA) access mechanism is proposed. The access mechanism forces MTs with reception errors during a collision resolution epoch to transmit more than P times. Analytical models for Poisson traffic are proposed for the throughput and delay. The proposed system’s performance is evaluated for a Single-Carrier with Frequency Domain Equalization (SCFDE) scheme, and compared to classical NDMA. H-NDMA parameter configuration is defined in terms of Quality of Service (QoS) requirements